Analisis Efektifitas Dan Efisiensi Pelaksanaan Anggaran Belanja Studi Kasus LLDIKTI Wilayah I Sumut - Ainun Nahya Dwi Arizona; Juliana Juliana (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
Public sector organizations are required to pay attention to Value for Money in carrying out their activities. The desired objective is to include accountability regarding the implementation of value for money, namely the economy in procurement and efficient resource allocation in the use of resources in the sense that their use is minimized and the results are maximized and effective in the sense of achieving goals and objectives. This research is the result of observations that show the facts and explain the nature that occurs in the object under study. This study aims to determine and analyze the effectiveness and efficiency of the LLDIKTI Region I North Sumatra Medan expenditure budget for the 2018-2021 period. In this study, it can be seen whether the implementation of the LLDIKTI Regional I North Sumatera Medan budget has been effective and efficient in it. The type of research used in this research is descriptive research using a qualitative approach. Data collection techniques were carried out by means of observation and literature study. The theory used to determine and analyze the effectiveness and efficiency of budget implementation is the analysis and calculation of the level of effectiveness and efficiency. Based on the results of this study, it shows the level or criteria for budget effectiveness at LLDIKTI Region I North Sumatra Medan from 2018-2021. In its implementation, the 2018-2021 budget as a whole is effective. And in 2018, 2019 and, 2021 was included in the fairly efficient category, while in 2020 there was an increase so that it was included in the efficient category.